Effective harvesting of microalgae: Comparison of different polymeric flocculants. (March 2017) - Gerchman, Yoram; Vasker, Barak; Tavasi, Mordechai; Mishael, Yael; Kinel-Tahan, Yael; Yehoshua, Yaron
Graphical abstract: Highlights: Microalgae are promising feed stock for biofuels but harvesting is a major hurdle. PDADMAC, used for water treatment, can be used for sedimentation of such algae. This polymer was effective at 5 mg/L, with fast kinetics and stable sedimentation over wide pH range. Achieving zeroing of Zeta potential is not needed for effective sedimentation. This flocculant could be used for effective low-cost microalgae flocculation. Abstract: Microalgae harvesting is a major hurdle in the use of microalgae for oil production. Here we describe the use of a standard cationic polymer used for water treatment, Polydiallyldimethylammonium chloride (PDADMAC), for sedimentation of Chlorella vulgaris and comparison of its flocculation properties with two other polymers, chitosan and Superfloc®. We found PDADMAC to be the most effective flocculant with 90% of the algae flocculating at concentrations as low as 5 mg/L within 60 min, and good activity even at pH = 10. Interestingly, with both PDADMAC and chitosan maximum flocculation was achieved much before zeroing of zeta potential. PDADMAC flocculation was also very effective in enhancing harvest by filtration and somewhat at flocculation and sedimentation of marine algae, Nannochloropsis salina .